Cystic hepatoblastoma in an adolescent: A case report - Aliou Zabeirou; Boubacar Efared; Adama Saidou; Fanta Ousseini; Djamila Abdourahmane Soli; Nafissa Abdou; James Didier Lassey; Rachid Sani (Journal of Pediatric Surgery Case Reports, 2024)
Introduction: Hepatoblastoma accounts for approximately 1 % of pediatric tumors. It occurs mainly between 6 months and 3 years of age and is extremely rare in adolescents and adults. Hepatoblastoma generally presents as a painless abdominal mass discovered incidentally. We report a case of painful cystic hepatoblastoma in an adolescent, that was initially thought to be an amebic liver abscess. Case presentation: A 15-year-old male with no significant medical history was admitted to the emergency department with right hypochondrium pain, fever, and vomiting for 14 days. Abdominal examination revealed hepatomegaly with a tender liver, firm surface, and well-defined inferior edge. A contrast-enhanced abdominal CT scan was done, demonstrating a suspected amebic liver abscess in segments S4 – S5. The patient was taken to the operating room. The abscess was punctured and drained, and a biopsy of the wall was taken. All this was done laparoscopically. The pathology of the cyst wall was consistent with hepatoblastoma. The patient was brought back to the operating room after 3 weeks and underwent a complete resection of the cystic tumor through a partial hepatectomy. The patient's postoperative course was uneventful, and he was discharged 5 days after the operation. Histological examination of the surgical specimen confirmed the diagnosis of hepatoblastoma. Conclusion: Hepatoblastoma is extremely rare in adolescents. Cystic hepatoblastoma should be included in the differential diagnosis of a hepatic cyst, regardless of the patient's age, even in areas where infectious hepatic cysts are widely prevalent.